Numerical study of a semi-passive oscillating hydrofoil on power-extraction with wing-in-ground effect. (November 2022) - He, Guanghua; Mo, Weijie; Gao, Yun; Wang, Jiadong; Zhang, Zhigang; Yang, Hao; Mao, Weihao
Abstract: The performance of a semi-passive oscillating hydrofoil, with activated pitching motion and induced heaving motion, is numerically studied by OpenFoam. The two-dimensional incompressible Navier–Stokes equations are solved using a finite-volume numerical method coupling with an overset grid technique. First, the fluid–structure interaction problem involved in the dynamics of an oscillating hydrofoil with an energy harvesting system is examined. The two-dimensional analysis allows us to simulate dynamics of oscillating hydrofoil system over a large range of parameters for identifying the optimal areas for power extraction. A maximum efficiency of η = 39 . 90 % is achieved with an optimal set of parameters. The efficiency stays at a relatively high level with little variation in a large range of damping coefficient, providing a flexible selection for designers in practical applications. Thereafter, we concentrate on the wing-in-ground (WIG) effect, which has been reported as a great potential to improve the power extraction for oscillating hydrofoils. When the hydrofoil approaches the ground, a Venturi channel can be formed between the hydrofoil and the ground, which leads to a good timing of vortex–foil interactions. Benefit from the WIG effect, the amount of power extraction has a significant increase.